Influence of Political Risk on International Business Operations in Germany - Bruno, Conrad (International Journal of Modern Risk Management, 2024)
Purpose: The aim of the study was to investigate the influence of political risk on international business operations in Germany. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed that political uncertainties, such as shifts in government policies, geopolitical tensions, and regulatory changes, can significantly impact the business environment, investment decisions, and market opportunities in Germany. While Germany is known for its stable political system and business-friendly environment, recent developments, such as Brexit, global trade tensions, and the rise of nationalist movements, have introduced new layers of complexity and uncertainty for international businesses operating in the country. These political risks can manifest in various forms, including disruptions to supply chains, fluctuations in currency markets, and heightened regulatory scrutiny, necessitating proactive risk management strategies and adaptive business practices. Unique Contribution to Theory, Practice and Policy: Institutional Theory, Resource Dependence Theory (RDT) & Transaction Cost Economics (TCE) theory may be used to anchor future studies on influence of political risk on international business operations. Implement regular political risk assessments using this comprehensive framework to identify potential threats and opportunities in different regions. Businesses should use advanced analytics and scenario planning to forecast potential political changes and their impacts. Businesses should diversify their investments across multiple countries and regions with varying political risk profiles. Policymakers should establish standardized guidelines for political risk assessment to ensure consistent and accurate evaluation across industries and regions. This will help firms better prepare for and mitigate political risks.